STUDI NERACA AIR DI KOTA JAMBI - Laypi, Siska Ilza; Juita, Erna; Febriana, Farida (STKIP PGRI Sumbar, 2013)
The degree of population density in urban area is very high, because of every year the number of population is high inhabitant development in the city, so it influence the availability of water in Jambi city. The purpose of this research is to calculate the water balance in Jambi city. The component of water balance are: rainfall, evapotranspiration, infiltration, and run off. This research was descriptive quantitative, which collected from varios institution in Jambi. To answer the problems of formulation can used secondary data, secondary data was reference source and analysis from library or institution. The result of this research was water balance for Jambi city. 1). The highest amount of rainfall in Jambi city happen in December, March and December with 246 mm/month and lowest rainfall happen in June with a mount rainfall 113.1 mm/month, whereas the mean yearly rainfall is was 2347.1 mm. 2) the highest infiltration happened in September as 98.89 mm and the lowest as 85.89 mm in May. 3). the high est evapotranspiration happen in Jambi city on May 12.784 mm. Then, the lower evapotranspiration happen in Jambi city on March 7.92 mm. 4). The surface run off was high and happened in Jambi city on November 146.06 mm, and the lowest surface run off was happened on August 43.69 mm. 5). The result of water balance in Jambi city, showed deficit of water on May, June, July, September, and November where the surplus on January, February, march, April, August, October, and December.